High-throughput screening identifies small molecule inhibitors of thioesterase superfamily member 1: Implications for the management of non-alcoholic fatty liver disease - Christopher S. Krumm; Renée S. Landzberg; Lavoisier Ramos-Espiritu; Carolina Adura; Xu Liu; Mariana Acuna; Yang Xie; Xu Xu; Matthew C. Tillman; Yingxia Li; J. Fraser Glickman; Eric A. Ortlund; et al. (Elsevier, 2023)
Objective: Thioesterase superfamily member 1 (Them1) is a long chain acyl-CoA thioesterase comprising two N-terminal HotDog fold enzymatic domains linked to a C-terminal lipid-sensing steroidogenic acute regulatory transfer-related (START) domain, which allosterically modulates enzymatic activity. Them1 is highly expressed in thermogenic adipose tissue, where it functions to suppress energy expenditure by limiting rates of fatty acid oxidation, and is induced markedly in liver in response to high fat feeding, where it suppresses fatty acid oxidation and promotes glucose production. Them1−/− mice are protected against non-alcoholic fatty liver disease (NAFLD), suggesting Them1 as a therapeutic target. Methods: A high-throughput small molecule screen was performed to identify promising inhibitors targeting the fatty acyl-CoA thioesterase activity of purified recombinant Them1.Counter screening was used to determine specificity for Them1 relative to other acyl-CoA thioesterase isoforms. Inhibitor binding and enzyme inhibition were quantified by biophysical and biochemical approaches, respectively. Following structure-based optimization, lead compounds were tested in cell culture. Results: Two lead allosteric inhibitors were identified that selectively inhibited Them1 by binding the START domain. In mouse brown adipocytes, these inhibitors promoted fatty acid oxidation, as evidenced by increased oxygen consumption rates. In mouse hepatocytes, they promoted fatty acid oxidation, but also reduced glucose production. Conclusion: Them1 inhibitors could prove attractive for the pharmacologic management of NAFLD.